Li6PS5Cl-based composite electrolyte reinforced with high-strength polyester fibers for all-solid-state lithium batteries - Lee, Si-Eun; Sim, Hui-Tae; Lee, Young-Jun; Hong, Seung-Bo; Chung, Kyung Yoon; Jung, Hun-Gi; Kim, Dong-Won (ELSEVIER, 2022)
All-solid-state lithium batteries (ASSLBs) with sulfide electrolytes attract considerable attention owing to their enhanced safety and high energy density compared to lithium-ion batteries employing liquid electrolytes. However, the conventional cold pressing method for preparing solid electrolyte pellets causes the formation of large pores in the electrolyte. Alternatively, hot pressing the pellets is an effective method for densifying the solid electrolyte and enhancing its ionic conductivity. However, hot-pressed sulfide electrolytes are brittle and difficult to handle, and must be thick to maintain their dimensional stability without cracking during the hot-pressing process. Herein, we prepare a thin, dense Li6PS5Cl (argyrodite)-based composite electrolyte reinforced with high-strength polyester fibers. A composite electrolyte reinforced with 5.0 wt% fiber exhibits high ionic conductivity of 2.9 x 10(-3) S cm(-1) and much higher ionic conductance than pristine Li6PS5Cl pellets. The interfacial contact between the composite electrolyte and composite cathode is also enhanced by additional hot pressing. The ASSLB (Li-In/LiNi0.7Co(0.1)Mn(0.2)O(2)) employing the composite electrolyte initially delivers a high discharge capacity of 185.7 mAh g(-1), corresponding to an areal capacity of 2.0 mAh cm(-2), and exhibits stable cycling performance with a capacity retention of 71% after 300 cycles at 0.2C and 25 ?.